Meningkatkan Kesadaran Kesehatan, Lingkungan dan Hukum di Desa Bina Baru Kecamatan Kampar kiri Tengah Kabupaten Kampar - Zulhendri, Zulhendri; Winario, Mohd; Ediputra, Kasman; Hidayat, Adityawarman (EL-EMIR INSTITUTE, 2024)
This service is aimed at the community of Bina Baru village, Kampar Kiri Tengah sub-district, Kampar regency, in order to increase awareness of health, the environment and the law. The purpose of this service is so that the community can know the benefits of keeping the community environment clean and be able to improve and maintain the cleanliness of the community environment, especially the family, as well as providing legal education. This service is carried out through counseling, socialization and discussion methods. In general, the program can be implemented well, on the other hand, the response and participation from the community is very good towards the programs that have been implemented in the field. Several things can be concluded from the results of the implementation of this activity, including: 1) almost all the fathers and mothers of the new bina villages are willing to take part in public health and environmental education. and they want to follow a clean lifestyle according to the presentation of the counseling material. 2) The positive enthusiasm and curiosity of the mothers was shown by the various questions asked during the delivery of the material and during the counseling, and 3) Based on the results of the friendly communication between the Community Service team and the PKK mothers and village officials, they hoped that similar activities would be carried out routinely. with the addition of materials such as checking cholesterol and uric acid levels.